Integrated care : reflections on change in health services - Kaehne, Axel (Emerald points., 2022)
Over the last twenty years integrated care has been touted as a solution to many issues in health services, such as insufficient coordination between services, cumbersome organizational boundaries, interrupted patient journeys, as well as spiraling health care costs. However, despite volumes of research, the field has seen few innovative advances in recent years. In particular, prevailing integrated care implementation practice and research appear to be very health science centred, spurning approaches from other disciplines. Axel Kaehne argues that it is time to re-evaluate how we investigate care integration. He asks us to radically question our assumptions about integrated care as a managerial, organisational and behavioural endeavor. This is a profound departure from conventional thinking about integration in health and social care. Kaehne reveals the tacit assumptions we make when we manage and change health services and offers a fresh perspective on care integration whilst inviting readers to examine long established research orthodoxies. This eclectic conceptual and theoretical approach produces surprising insights for everyone who is ready to see things anew.